Effect of different monomers on water retention properties of slow release fertilizer hydrogel - Rabat, N. E. (Elsevier Ltd, 2016)
The combination of hydrogel and fertilizer as slow release fertilizer hydrogel (SRFH) has become one of the promising materials to overcome the shortcomings of conventional fertilizer by decreasing fertilizer loss rate, supplying nutrients sustainably, and lowering frequency of irrigation. A comparative study on water retention and plant growth performances of SRFH made from three hydrophilic monomers; acrylic acid (AA), acrylamide (AAm) and AA-co-AAm was executed. PAA SRFH has smaller swelling rate constant, k as it required only 166.67 minutes to absorb 0.63 of its equilibrium capacity of swelling, followed by P(AA-co-AAm) SRFH and PAAm SRFH. Although PAAm SRFH has the lowest swelling rate constant, it has the most excellent water retention ability in soil followed by P(AA-co-AAm) SRFH. Additionally, the presence of PAA SRFH in soil has enhanced the plant growth performances of model plant (capsicum annum) in term of its average leaf width and plant height. The synergistic effects of acrylic acid and acrylamide in P(AA-co-AAm) SRFH could be utilized to produce hydrogel used in agriculture.